ANALISIS IMPLEMENTASI TRANSKASI NON TUNAI PADA PEMERINTAH DAERAH KABUPATEN MALUKU TENGGARA - Andreas Charles Tetan El; Steven Siaila (Soso-Q : Jurnal Manajemen, 2021)
ABSTRACT Regional Original Revenue (PAD) is an important element in the income of a region, because if PAD can be increased, it will directly have an impact on the independence of the regional government. This rationale is the purpose of writing about the Implementation of Non-Cash Transactions in Southeast Maluku Regency. It is hoped that with the implementation of non-cash transactions, payment of regional taxes and regional levies will be easy to do and trigger an increase in PAD.The quantitative descriptive analysis method is the method used in this paper. Data regarding the realization of monthly regional tax and levy payments from January to May 2021 serve as basic data to determine the size of the sample for each object of local tax levy and regional levies in Southeast Maluku Regency. By utilizing the questionnaire obtained a sample of 10% of each object of local taxes and levies. If theobject of local taxes and regional levies is less than 5 taxpayers or levies are taken as a whole. The sample results obtained are as many as 56 samples. The perception data of local taxpayers and local levies provide their perceptions according to the questionnaire used. The results of the analysis obtained are that the benefit aspect has a positive and significant effect on the implementation of non-cash transactions in Southeast Maluku Regency; The Convenience Aspect has a positive and significant effect on the implementation of non-cash transactions in Southeast Maluku Regency and the Benefit Aspect and the Convenience Aspect together have a positive and significant impact on the implementation of non-cash transactions in Southeast Maluku Regency. Based on these results, it can be said that the implementation of non-cash transactions will be able to become an alternative for PAD intensification in Southeast Maluku Regency.Keywords: Intensification of PAD Sources => Implementation of Non-Cash Transactions